Power, money and Russian distemper (about monograph of M. V. Khodyakov «Money of the Revolution and the Civil War: 1917–1920») - D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes monograph «The Money of the Revolution and the Civil War: 1917–1920», prepared by the head of the Department of Modern History of Russia at St. Petersburg State University, Doctor of History, Professor M. V. Khodyakov. The book is released in 2019 by the St. Petersburg State University Publishing House (St. Petersburg). It analyzed features of the author’s approach in covering financial history at a turning point in the functioning of Russian statehood during the Revolution and the Civil War. An attempt is made to analyze the most significant regularities of the interrelated development of the state-political and financialeconomic spheres. The scientific, methodological novelty of the monograph is noted, as well as certain aspects that are promising for further study of the problem covered in the reprinted work